Flower-like polyaniline/graphene hybrids for high-performance supercapacitor. (12th April 2017) - Ke, Fuyou; Liu, Yu; Xu, Hongyao; Ma, Yu; Guang, Shanyi; Zhang, Fayin; Lin, Naibo; Ye, Meidan; Lin, Youhui; Liu, Xiangyang
Abstract: A novel flower-like polyaniline/graphene hybrid (PANI-ATRGO) is prepared by a one-pot synthesis and used as electrode materials for supercapacitors. The structure, formation mechanism and electrochemical properties of such unique architecture are systematically investigated by combining Fourier transform infrared spectroscopy, Ultraviolet–visible absorption spectroscopy, Raman spectroscope, X-ray diffraction and electrochemical techniques. The results suggest that "V-type" amino groups of ATRGO and supermolecular assembly between PANI chains play the key role in the formation of flower-like nanostructures. Compare to pristine PANI (487 F g −1 at 1 A g −1 ), PANI-ATRGO electrode materials exhibit a remarkable improvement of the specific capacitance (1510 F g −1 at 1 A g −1 ) for supercapacitor in addition to excellent rate capacity and long-term cycling stability. Moreover, it is found that flower-like PANI-ATRGO hybrids exhibit better electrochemical properties than the corresponding nanorod-array hybrids in our previous study. This reveals the significance of controlling the hierarchical structure of hybrid materials in the development of high-performance supercapacitor.